THE ROLE OF CYTOKINES TNF-Α, IFN-Γ, IL-1, IL-4, IL-8 IN THE IMMUNE RESPONSE IN INFECTIOUS LESIONS OF CNS IN CHILDREN - S. N. Eshmolov; I. G. Sitnikov; I. M. Melnikova (LLC "Diagnostics and Vaccines", 2018)
In recent years, a lot of attention has been paid to studying the level of cytokines in various infectious pathologies, since this scientific direction is rightly promising and justified. The article presents literature data on the significance of the cytokine link in the immune response and the results of our own observations of 108 patients aged 3 to 17 years with enteroviral meningitis. In addition to the standard diagnostic plan, all patients underwent immunological examination of blood serum in the acute phase of the disease in order to assess the level of cytokines (TNF-α, IFN-γ, IL-1, IL-4, IL-8). The analysis of the obtained data made it possible to establish correlations of different levels between the values of cytokines and other parameters.